The Numismatic chronicle. - Brooke, G. C. (George Cyril), 1884-; Hill, George Francis, Sir, 1867-1948; Codrington, O. (Oliver), -1921; Rapson, E. J. (Edward James), 1861-1937; Grueber, Herbert A. (Herbert Appold), 1846-1927; Head, Barclay Vincent, 1844-1914; Madden, Frederic W. (Frederic William); Vaux, W. S. W. (William Sandys Wright), 1818-1885.; Evans, John, Sir, 1823-1908; Akerman, John Yonge, 1806-1873; Royal Numismatic Society (Great Britain) (London., 1838)
List of members in each volume beginning with new ser., v. 1 (except new ser., v. 3).
Proceedings of the society are included in each volume, beginning with v. 5 (except v. 10, 19, and new ser., v. 4).
With v. 1 is bound; Horta, de, chevalier. Catalogue d'une partie de la collection de médailles. Londres, J. Wertheimer.
"Charter, bye-laws and regulations of the Royal Numismatic Society" bound with 4th ser., v. 4.
Editors: 18 -1857/58, J.Y. Akerman; 1856/57-1885, W.S.W. Vaux; 1861-1907, Sir J. Evans; 1861-68, F.W. Madden; 1869-1910, B.V. Head; 1885-1912, H.A. Grueber; 1898-1910, E.J. Rapson; 1911- Oliver Codrington; 1912-G.F. Hill; 1913- G.C. Brooke.
Title varies slightly.
"Journal of the Numismatic Society."
Mode of access: Internet.
English and French.
Vol. 1-10, in v. 11; vol. 1-20, in v. 20; new ser., v. 1-10, in v. 10; New ser., v. 11-20, in v. 20; 3d ser., v. 1-10, in v. 10; 3d sr., v. 11-20, in v. 20; 4th ser., v. 1-10, in v. 10; 4th ser., v. 11-20, in v. 20.
Keywords: Numismatics -- Periodicals